HUBUNGAN KUALITAS PELAYANAN DEPARTEMEN FRONT OFFICE DENGAN KEPUASAN TAMU MENGINAP DI HOTEL BUMIMINANG PADANG - Kurnia, Yofi; Silfeni, Silfeni; Chair, Ira Meirina (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The purpose of this research are: 1) Describe the quality of front office employee services Bumiminang Hotel Padang, 2) Describe the satisfaction of guest stay Bumiminang Hotel Padang, and 3) Analyze the relationship between the quality of service front office department with the satisfaction of guests staying at Bumiminang Hotel Padang.This type of research is correlational. The study population is all guests staying at Hotel Bumiminang Padang. Sample of 87 guests taken with certain criteria. Technique of data collection is done by using questionnaires that have been tested the validity and reliability. Further data is analyzed descriptively and correlation with the help of SPSS Computer Program version 20.00.The results of the study found that: 1) Quality of front office services are in very good category (44%), 2) Satisfaction of guests staying in Good category (45%), 3) Product Moment Correlation test results show a positive relationship (strong enough ) And significant between Quality of Front Office Service and Customer Satisfaction at Hotel Bumiminang Padang with r value of 0,804 are at 0,75-0,99 and at Sig 0,000 level.